Reliable Ala-Tragus Line for the Orientation of Occlusal Plane by Cephalometry - Shrestha, Lajana; Joshi, S.P. (Journal of Nepalese Prosthodontic Society, 2018)
Introduction: The aim of the study was to determine the most reliable ala-tragus line for the orientation of the occlusal plane in edentulous patients during complete denture fabrication by cephalometry. Materials and Methods: Lateral cephalometric radiographs of 37 dentate subjects were taken at maximum intercuspation. Steel balls were used as radio opaque markers which were adhered to superior border, middle point, and inferior border of tragus as well as the inferior border of ala of nose. Lead foil was cemented to cover the mesio-palatal cusp of maxillary first molar. Tracings of cephalogram were done. Angle between ala-tragus superior, ala-tragus middle and ala-tragus inferior in relation to occlusal plane were measured. Variables were determined and data were analyzed using SPSS version 17 (SPSS, Inc. Chicago, III). Results: The angle formed between occlusal plane and ala tragus middle had lowest mean value of 2.39°. The highest was measured with ala tragus superior 5.18°, while the angle formed with ala tragus inferior was 3.60°. The differences between the three planes in relation to the occlusal plane were significantly different in total subjects as well as in both males and females (p < 0.001). Conclusion: Statistical analysis showed that the middle point of the tragus with the inferior border of the ala of the nose was most accurate in orienting the occlusal plane.